RETHINKING CAPITAL PUNISHMENT IN INDONESIA: LEGAL FRAMEWORK AND PATHS TO ABOLITION - Satrio, Pandu Adi; Yahya, Azhari (Universitas Syiah Kuala, 2024)
The debate over the death penalty remains unresolved, with mixed opinions from legal professionals and human rights activists. In many Asian countries, discussions about international human rights and abolition treaties often face limitations, as they can be viewed as forms of cultural imperialism. This paper explore the implementation of the death penalty in Indonesia, examining the reasons for its continued use and analyzing steps that the Indonesian government could take to abolish it in line with the International Covenant on Civil and Political Rights (ICCPR). The research is normative legal research, which focuses on identifying legal rules, principles, and doctrines to address existing legal issues. It seeks to generate arguments, theories, and new concepts that can contribute to solving these problems. The findings indicate that the death penalty remains entrenched in Indonesia's legal system despite ongoing debates about its application. Many still view the death penalty as necessary, believing it aligns with human rights standards and Islamic principles. However, Indonesia has options for moving towards abolition, such as instituting a moratorium on the death penalty. It is recommended that the House of Representatives review all laws imposing the death penalty and mandate institutions to reassess cases where this penalty has been applied, potentially commuting sentences. The government can also consider implementing a moratorium on the death penalty as a step towards eventual abolition.